Some Consequences of Categorification - Rupel, Dylan; Stella, Salvatore (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
Several conjectures on acyclic skew-symmetrizable cluster algebras are proven as direct consequences of their categorification via valued quivers. These include conjectures of Fomin-Zelevinsky, Reading-Speyer, and Reading-Stella related to d-vectors, g-vectors, and F-polynomials.